Implementation of a Web-Based Waste Collection Data System Using QR Code Scanning - Romadhon, Ibrahim Aji Fajar; Rohman, Arif Nur; Pristyanto, Yoga (Sistemasi: Jurnal Sistem Informasi, 2025)
The suboptimal management of waste collection in urban areas significantly impacts environmental quality and public health. Yogyakarta City, which generates 644.69 tons of waste annually, can only manage 583.80 tons per year. Various initiatives have been implemented to improve waste management, yet challenges persist, such as limited temporary disposal sites, irregular waste collection schedules, and the absence of an effective and efficient system to assist waste collection officers in recording and tracking waste collection for each household.This study aims to develop a web-based Waste Collection Data System using QR Code Scanning, employing the waterfall method, which consists of the following stages: requirement analysis, design, development, testing, and maintenance. The system enables waste collection officers to log waste collection activities by scanning a QR code at each household and allows residents to access information regarding waste collection status, mandatory fees, collection schedules, and waste processing. The testing results demonstrate that all features function effectively as intended. The implementation of this system is expected to enhance the efficiency of waste collection data management, improve environmental quality, and increase community satisfaction in Yogyakarta City.